MARINE HARMFUL ALGAL BLOOMS (HABs) IN WORLD’S TOURIST REGIONS - Jaworska, Bożena (Polish Journal of Natural Sciences, 2024)
Harmful algal blooms (HABs) include toxic and non-toxic blooms of microalgae and macroalgae that are detrimental to aquatic ecosystems, have negative impacts on human health or socio-economic interests. All of these aspects are important for tourism and recreation related to marine areas, coastal waters, shorelines and coastal areas. They reduce the attractiveness of the regions in which they occur and can be a determinant of directional preferences for tourism activities. The aim of this study is to analyse the occurrence of typical HABs in tourist regions of the world, taking into account the taxa that cause them and the threats they pose. The analysis is based on a review of knowledge on the subject. It outlines the magnitude of the problems associated with the occurrence of HABs and demonstrates their relationship to the tourism sector. It also indicates the need for the tourism sector to obtain information on HABs in order to verify the availability of safe destinations for tourism.